Health problems of adolescents and their implications for health education - Contreras, Ma. Fe C. 1933-
The aim of this study is to identify the health problems of high school students in Calinog Agricultural and Industrial School. Specifically, it sought to determine the problems of the students along the following health areas: personal health, nutrition, boy-girl relationship, safety and accidents, communicable and non-communicable diseases, and drug use, misuse and abuse.